Optimal 10-Aminoartemisinins With Potent Transmission-Blocking Capabilities for New Artemisinin Combination Therapies–Activities Against Blood Stage P. falciparum Including PfKI3 C580Y Mutants and Liver Stage P. berghei Parasites - Wong, Ho Ning; Padín-Irizarry, Vivian; van der Watt, Mariëtte E.; Reader, Janette; Liebenberg, Wilna; Wiesner, Lubbe; Smith, Peter; Eribez, Korina; Winzeler, Elizabeth A.; Kyle, Dennis E.; Birkholtz, Lyn-Marie; Coertzen, Dina; et al. (Frontiers in Chemistry, 2020)
We have demonstrated previously that amino-artemisinins including artemiside and artemisone in which an amino group replaces the oxygen-bearing substituents attached to C-10 of the current clinical artemisinin derivatives dihydroartemisinin (DHA), artemether and artesunate, display potent activities in vitro against the asexual blood stages of Plasmodium falciparum (Pf). In particular, the compounds are active against late blood stage gametocytes, and are strongly synergistic in combination with the redox active drug methylene blue. In order to fortify the eventual selection of optimum amino-artemisinins for development into new triple combination therapies also active against artemisinin-resistant Pf mutants, we have prepared new amino-artemisinins based on the easily accessible and inexpensive DHA-piperazine. The latter was converted into alkyl- and aryl sulfonamides, ureas and amides. These derivatives were screened together with the comparator drugs DHA and the hitherto most active amino-artemisinins artemiside and artemisone against asexual and sexual blood stages of Pf and liver stage P. berghei (Pb) sporozoites. Several of the new amino-artemisinins bearing aryl-urea and -amide groups are potently active against both asexual, and late blood stage gametocytes (IC50 0.4-1.0 nM). Although the activities are superior to those of artemiside (IC50 1.5 nM) and artemisone (IC50 42.4 nM), the latter are more active against the liver stage Pb sporozoites (IC50 artemisone 28 nM). In addition, early results indicate these compounds tend not to display reduced susceptibility against parasites bearing the Pf Kelch 13 propeller domain C580Y mutation characteristic of artemisinin-resistant Pf. Thus, the advent of the amino-artemisinins including artemiside and artemisone will enable the development of new combination therapies that by virtue of the amino-artemisinin component itself will possess intrinsic transmission-blocking capabilities and may be effective against artemisinin resistant falciparum malaria.